Penyelesaian Sengketa atas Video dan Foto Resepsi Pernikahan Hilang Perspektif Kompilasi Hukum Ekonomi Syariah - Aricanes, Erisando; Zahara, Fatimah (IAI Darussalam, 2024)
Settlement of disputes in al-ijarah contract transactions between service providers (mu'jir) and service recipients (musta'jir) in Medan City, is sometimes carried out not in accordance with the instructions contained in Supreme Court Regulation Number 02 of 2008 concerning the Compilation of Sharia Economic Law (KHES). This can be seen, when a musta'jir in the city of Medan demands compensation from the mu'jir with an amount that is very burdensome for the mu'jir, even though the actual condition of the mu'jir is not breaking a promise, but because of a compelling or emergency condition caused by losing your laptop, burning your hard disk, or video and photo files being infected by a virus so that the data is lost and it is difficult to restore the data to how it was originally. Mu'jir has broken his promise if seen at a glance as stated in Article 36 starting from letter